Vocalization behaviors in captive bottlenose dolphins (Tursiops truncatus) and rough-toothed dolphins (Steno bredanensis) - Weijie Fu; Zhongchang Song; Wenjie Xiang; Chuang Zhang; Wuyi Yang; Xiaohui Xu; Yu Zhang (PLoS ONE, 2025)
Odontocetes rely on vocalizations for navigation, foraging, and communication. Their vocalization patterns are associated with environmental conditions and behavioral contexts, particularly in captive populations. This study investigated the vocalization behaviors of captive bottlenose dolphins ( Tursiops truncatus ) and rough-toothed dolphins ( Steno bredanensis ) using continuous acoustic monitoring. The focus was on their responses to human-involved training and feeding activities. Comparative analyses revealed that rough-toothed dolphins produced significantly more clicks and fewer whistles than bottlenose dolphins ( p < 0.05). During training, bottlenose dolphins reduced their click rate by 41% but increased whistle production by 125%. In contrast, rough-toothed dolphins showed no significant change in click emissions (from 643.9/min to 597.4/min, p > 0.05), but significantly reduced whistles by 56% ( p < 0.05). Neither species exhibited significant changes in vocalization during feeding. However, rough-toothed dolphins shifted their predominant whistle type from “constant” to “sinusoidal”, while bottlenose dolphins changed from “constant” to “upsweep” during feeding. These findings offer valuable insights expanding current knowledge of dolphin vocal patterns under captivity and establish baseline information potentially supporting acoustic assessment of captive dolphin welfare, particularly for the understudied rough-toothed dolphin.